Assessment of imatinib as first-line treatment of chronic myeloid leukemia: 10-year survival results of the randomized CML study IV and impact of non-CML determinants - Hehlmann, Rüdiger; Saußele, Susanne; Fabarius, Alice; Kohlbrenner, Katharina; Voskanyan, Astghik; Rinaldetti, Sébastien; Seifarth, Wolfgang; Spiess, Birgit; Ho, Anthony Dick (Leukemia, 2017)
Chronic myeloid leukemia (CML)-study IV was designed to explore whether treatment with imatinib (IM) at 400 mg/day (n=400) could be optimized by doubling the dose (n=420), adding interferon (IFN) (n=430) or cytarabine (n=158) or using IM after IFN-failure (n=128). From July 2002 to March 2012, 1551 newly diagnosed patients in chronic phase were randomized into a 5-arm study. The study was powered to detect a survival difference of 5% at 5 years. After a median observation time of 9.5 years, 10-year overall survival was 82%, 10-year progression-free survival was 80% and 10-year relative survival was 92%. Survival between IM400 mg and any experimental arm was not different. In a multivariate analysis, risk group, major-route chromosomal aberrations, comorbidities, smoking and treatment center (academic vs other) influenced survival significantly, but not any form of treatment optimization. Patients reaching the molecular response milestones at 3, 6 and 12 months had a significant survival advantage. For responders, monotherapy with IM400 mg provides a close to normal life expectancy independent of the time to response. Survival is more determined by patients’ and disease factors than by initial treatment selection. Although improvements are also needed for refractory disease, more life-time can currently be gained by carefully addressing non-CML determinants of survival.